CONCOMITANCE OF ROTATOR CUFF DISEASE IN SYMPTOMATIC ANTERIOR SHOULDER INSTABILITY - Tsvetan Tsenkov; Alexander Gerchev (Peytchinski Publishing, 2022)
Purpose: To evaluate the concomitance of rotator cuff disease in patients with symptomatic anterior shoulder instability and its impact on the severity of lesions. Materials and Methods: Retrospective data were collected from 326 patients from a single institution for a 16-year period. The demographic characteristics of the patients were selected randomly. The leading diagnosis was shoulder instability. Excluded from the study were patients with posterior (n=24) or mixed instability (n=5). Primary diagnosis was confirmed with clinical findings and MRI imaging studies. All patients from the group underwent arthroscopic surgery. A throughout analysis was performed of the collected materials. Results: 297 patients with primary anterior instability underwent arthroscopic stabilization in the clinic. 25% (n=75) presented with different grade rotator cuff lesions, of which only 33% (n=25) were discovered on MRI preoperatively. In these patients, rotator cuff tenoplasty was performed. In 27% (n=79) of the patients, an evident subacromial space narrowing without rotator cuff lesions was found during arthroscopy. In these cases, a subacromial decompression was performed, and in some of the cases - acromioplasty. In 52% (n=154) of patients who underwent an arthroscopic stabilization for anterior shoulder instability, additional treatment was necessary. Conclusions: The complex analysis of shoulder pathology can shield the surgeon from diagnostic misses and unsatisfactory results. Coexisting rotator cuff disease may have a role in symptomatic anterior shoulder instability as it is often neglected in clinical evaluations due to the main diagnosis of instability.